Inovasi Layanan Antar Jemput Paket Surat PT Pos Indonesia Berdasarkan Penjualan dan Minat Beli - Rahmayani, Rani; Firmansyah, Esa; Sariwaty S, Yulia; Ulil Hikmah, Hilda (Yayasan Lembaga Studi Makwa, 2025)
PT Pos Indonesia transformed with a service renewal, namely the Q9Plus service. The service refers to one of the products, namely package and mail transfers by providing pick-up officers and transportation facilities. The package and mail pick-up clerk is called an O-Ranger. This fulfillment aims to make it easier for officers when picking up, picking up, and processing. The innovation of package and mail pick-up services is utilized by several online shops to facilitate the delivery of goods. Thus, the sale of PT Pos Indonesia's Cibatu Garut Branch has changed so that the service can attract consumer interest and attention. The purpose of this study was to determine the interrelation of sales and consumer buying interest on the innovation of parcel and mail shuttle services at PT Pos Indonesia Cibatu Garut Branch. The method in this study is a quantitative method with a descriptive and verification research design. Determination of the sample using the Lemeshow formula and the acquisition of as many as 96 respondents with probability sampling method and stratified random sampling technique. Respondents in this study were the people of Cibatu Garut District. This study uses the SPSS (Statistical Product and Service Solutions) program which aims to measure the effect of sales and buying interest on the innovation of parcel and mail delivery services at PT Pos Indonesia Cibatu Garut Branch and uses the t and F hypothesis tests to find out partially and simultaneously. The results showed that partially sales and buying interest had a positive and significant effect on innovation.